Hierarchical p-n heterostructure BiOI@ZnTi-LDH for Cr(VI) reduction under visible light - Xiong, Jie; Zeng, Hong-Yan; Chen, Chao-Rong; Xiao, Gao-Fei; An, De-Shun (Journal of alloys and compounds, 2020)
The hierarchically core-shell BiOI@Zn/Ti hydrotalcite (LDH) composites with p-n heterostructure was successfully prepared by layer-by-layer self-assembly using a facile hydrothermal method, where the ZnTi-LDH nanoplatelets were coated on the BiOI core to form the flower-like BiOI@ZnTi-LDH microspheres. The morphology, microstructure, surface properties, photoelectric performances and visible-light response of the BiOI@ZnTi-LDH were also investigated in detail. Comparing to the single BiOI and ZnTi-LDH components, the p-n heterostructure BiOI@ZnTi-LDH indicated excellent enhanced photocatalytic activity for hexavalent chromium (Cr(VI)) reduction under visible-light irradiation (λ > 420 nm), which was imputed to the efficient combination of the unique 3D hierarchical core-shell structure and p-n heterojunction endowing the photogenerated electronhole pairs with efficient transfer and separation abilities. At the same time, In virtue of spectroscopy, Mott-Schottky and photoelectric techniques, the formation of p-n heterostructure and the charge transfer between BiOI and ZnTi-LDH were determined. So, this work provided a promising approach for the design and construction of smart 3D hierarchical core-shell materials in environmental treatment. [Display omitted] •Hierarchical BiOI@ZnTi-LDH core-shell material with p-n heterostructure was prepared using a simple hydrothermal method.•ZnTi-LDH nanoplatelets were coated on the BiOI core to form the BiOI@ZnTi-LDH microspheres with unique 3D structure.•The enhanced photoreduction performances were to the formation of p-n heterojunction and unique 3D structure.